Plädoyer für einen Ersatz der Grunderwerbsteuer - Wolfgang Scherf; Carolin Dresselhaus (Wirtschaftsdienst, 2016)
Seit der Föderalismusreform 2006 dürfen die Länder den Steuersatz der Grunderwerbsteuer auf die bundeseinheitliche Bemessungsgrundlage selbst bestimmen. Diese auf die Grunderwerbsteuer beschränkte Steuerautonomie der Länder erzeugte einen beachtlichen Anstieg der Steuerbelastung. Zehn Jahre nach der Reform ist es Zeit für eine Bilanz und eine Neuorientierung. Die Grunderwerbsteuer ließe sich relativ leicht in die Umsatzsteuer integrieren. – – Since Germany reformed its federal structure in 2006, federal states have been able to set their own rates of real-estate transfer tax. This limited tax autonomy at state level has resulted in a rate increase to 6.5%, which suggests that a narrow tax base is being exploited for purely fiscal purposes. The weaknesses of the real-estate transfer tax can be eliminated by integrating it into value-added tax. States' lost revenue can be offset by increasing their share of value-added tax. The resulting horizontal revenue shifts between federal states are an advantage compared with today's unjust tax burden differences.
Keywords: H24; H71; 330